Resource-efficient delivery of on-demand streaming data using UEP codes. - Lihao Xu
We propose and analyze a new multicast scheme for delivering on-demand streaming data using unequal protection codes. The scheme allows an end user to join only one multicast channel for a data stream at any time to play out the requested data stream from its beginning after a fixed initial playout delay. The scheme tolerates packet loss during transmission, and thus, significantly reduces the cost of implementing a reliable multicast network layer to ensure delivery of all packets. Meanwhile, resource usage of the scheme, including server computing bandwidth, network bandwidth, and client's buffer space, is determined only by the original data stream length and the initial playout delay, but is independent of either the number or the arrival pattern of individual end-user requests. Thus, the scheme is totally scalable with the number of end users, fully utilizing the data delivery efficiency of a multicast network. The scheme also uses resources efficiently, e.g., with an initial playout delays of 30 s and 60 s, multicasting a 2 h video using this scheme needs only about 5.5 and 4.8 times, respectively, the server computing bandwidth and network bandwidth of those for a single unicast delivery of the same original data stream.
Keywords: 2 h; 30 s; 60 s; UEP codes; Buffer space; Error-control codes; Multicast channel; Multimedia communication; Network bandwidth; On-demand streaming data; Packet loss; Playout delay; Reliable multicast; Server computing bandwidth; Streaming media; Unequal error protection; Unequal protection codes